Repigmentation of Tenacious Vitiligo on Apremilast - Sara B. Huff; Lorie D. Gottwald (Case Reports in Dermatological Medicine)
Vitiligo is a common pigment disorder characterized by acquired loss of function or absence of melanocytes, leading to distinct areas of depigmentation. Physical exam reveals sharply demarcated, depigmented macules or patches on otherwise normal skin. Vitiligo can present at any age, in any skin color. There is no specific serologic marker for diagnosis, but patients often have other autoimmune problems. Treatment options are limited and are difficult given the fact that the pathogenesis of the disease is not well elucidated. We present the case of a 52-year-old woman with vitiligo for over 2 decades. The patient’s medical history reveals a lack of response to many different approaches. This case highlights the ability of apremilast, an FDA-approved drug for the treatment of psoriasis and psoriatic arthritis, to achieve repigmentation in a case a vitiligo that has been extremely recalcitrant.